2006
DOI: 10.1152/ajpendo.00023.2006
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate ingestion does not alter skeletal muscle AMPK signaling during exercise in humans

Abstract: There is evidence that increasing carbohydrate (CHO) availability during exercise by raising preexercise muscle glycogen levels attenuates the activation of AMPKalpha2 during exercise in humans. Similarly, increasing glucose levels decreases AMPKalpha2 activity in rat skeletal muscle in vitro. We examined the effect of CHO ingestion on skeletal muscle AMPK signaling during exercise in nine active male subjects who completed two 120-min bouts of cycling exercise at 65 +/- 1% V(O2 peak). In a randomized, counter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
29
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 46 publications
4
29
1
Order By: Relevance
“…In addition, high levels of the NO donor sodium nitroprusside activate AMPK␣1 in rat skeletal muscle (9). However, in the present study, AMPK activation during contractions, as indicated by AMPK␣ Thr172 phosphorylation (28,29) and ACC␤ phosphorylation, was unaffected by L-NAME infusion (Fig. 5).…”
Section: Discussioncontrasting
confidence: 50%
“…In addition, high levels of the NO donor sodium nitroprusside activate AMPK␣1 in rat skeletal muscle (9). However, in the present study, AMPK activation during contractions, as indicated by AMPK␣ Thr172 phosphorylation (28,29) and ACC␤ phosphorylation, was unaffected by L-NAME infusion (Fig. 5).…”
Section: Discussioncontrasting
confidence: 50%
“…Glucose is another nutrient that could have potentially affected the stimulation of AMPK in the type 2 diabetes group. Akerstrom et al (44) reported that ingestion of a carbohydrate-containing drink, which caused a slight increase in plasma glucose levels, attenuated exercise-induced AMPK activation; yet, this finding was not confirmed by other investigators (45). We previously reported that lean type 2 diabetic subjects with elevated fasting plasma glucose concentrations achieve normal AMPK stimulation with exercise (18).…”
Section: Discussionmentioning
confidence: 88%
“…Unfortunately, it is difficult to determine from our chosen experimental design if the apparent enhanced AMPK signaling (and augmented p53 phosphorylation) in LOW is due to low glycogen per se and/or low circulating glucose availability caused by the absence of CHO feeding before, during, and after exercise. However, it is noteworthy that provision of glucose during exercise also attenuates AMPK activity (2), but this effect is only apparent when glucose feeding spares muscle glycogen utilization (25), thus suggesting that glycogen availability may be the predominant mechanism. We deliberately chose this extreme manipulation of CHO availability so as to initially determine whether there was an actual effect of CHO restriction, although further studies should now attempt to isolate which component of CHO restriction is most dominant.…”
Section: Discussionmentioning
confidence: 99%